2020
DOI: 10.3389/fphys.2020.01110
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopancreas Transcriptome Profiling Analysis Reveals Physiological Responses to Acute Hypoxia and Reoxygenation in Juvenile Qingtian Paddy Field Carp Cyprinus carpio var qingtianensis

Abstract: Fish Transcriptomic Responses to Hypoxia during the processes of hypoxia and reoxygenation is not a simple and reversible process. This work first reported the adaptive mechanism of hypoxia and the recovery mechanism of reoxygenation after hypoxia in common carp, and also provided new insights for the physiological regulation of fish under hypoxia treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 61 publications
2
7
0
Order By: Relevance
“…We speculate that this may inhibit glucose consumption in GIFT, and may result in hypoxia-induced damage to GIFT by triggering inflammation and insulin resistance. These results confirmed that in GIFT under hypoxia stress, anaerobic glucose metabolism is weakened and glucose homeostasis is imbalanced, which may be related to the increased death rate at 96 h. The metabolome analyses revealed increased contents of D-gluconate, N-acetyl-D-glucosamine, and N-acetyl-D-glucosamine-6-phosphate in the pentose phosphate pathway, indicating that this pathway was activated under acute hypoxia stress, similar to the results reported elsewhere [52]. Besides providing energy, the pentose phosphate pathway is also the main source of NADPH and ribose in the body [53], and it can provide raw materials for the synthesis of fatty acids, ribonucleic acids, and cholesterol.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We speculate that this may inhibit glucose consumption in GIFT, and may result in hypoxia-induced damage to GIFT by triggering inflammation and insulin resistance. These results confirmed that in GIFT under hypoxia stress, anaerobic glucose metabolism is weakened and glucose homeostasis is imbalanced, which may be related to the increased death rate at 96 h. The metabolome analyses revealed increased contents of D-gluconate, N-acetyl-D-glucosamine, and N-acetyl-D-glucosamine-6-phosphate in the pentose phosphate pathway, indicating that this pathway was activated under acute hypoxia stress, similar to the results reported elsewhere [52]. Besides providing energy, the pentose phosphate pathway is also the main source of NADPH and ribose in the body [53], and it can provide raw materials for the synthesis of fatty acids, ribonucleic acids, and cholesterol.…”
Section: Discussionsupporting
confidence: 90%
“…The metabolome analyses revealed increased contents of D-gluconate, N-acetyl-D-glucosamine, and N-acetyl-D-glucosamine-6-phosphate in the pentose phosphate pathway, indicating that this pathway was activated under acute hypoxia stress, similar to the results reported elsewhere [ 52 ]. Besides providing energy, the pentose phosphate pathway is also the main source of NADPH and ribose in the body [ 53 ], and it can provide raw materials for the synthesis of fatty acids, ribonucleic acids, and cholesterol.…”
Section: Discussionsupporting
confidence: 89%
“…Dissolved oxygen in the water directly affects energy metabolism, blood parameters, and physiological defense against oxidative stress in fishes, et al ( Wu, 2002 ). In fish, liver (PF-carp for hepatopancreas) are critical to metabolism ( Guilherme et al, 2012 ; Qi M et al, 2020 ). Changes in dissolved oxygen affect the physiological function of liver and disturb energy metabolism, antioxidant stress and the synthesis of other substances ( Almeida-Val et al, 2000 ; Wang and Richards, 2011 ; Jung et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the induction of hypoxia and thermal responsive genes in fish exposed to either water temperature and hypoxia stresses remains upregulated hours after returning to CTs and normal oxygen (i.e. 6–8 h; Buckley et al , 2006 ; Qi et al , 2020 ). Using molecular biomarkers specific to hypoxic and thermal stresses independently, we have demonstrated that during summer and early fall months when Cultus Lake exhibits profundal hypoxia and high water temperatures in the epilimnion, over one-third of the fish sampled were responding to hypoxic and thermal stresses concurrently.…”
Section: Discussionmentioning
confidence: 99%